LITERATURE EVALUATION OF SHARIA AUDITING IN ZAKAT MANAGEMENT ORGANIZATIONS: A SYSTEMATIC LITERATURE REVIEW - Yanti, Sri Devi; Abdullah, Muhammad Wahyuddin; Muchlis, Syaiful (UIN Sunan Gunung Djati Bandung, 2024)
The purpose of this study is to evaluate the literature related to sharia auditing in OPZ in Indonesia by conducting literature mapping. The research method used is systematic literature review. The literature search used the Google Scholar database with the help of the Publish or Perish 8 application. The article search was carried out using the keyword